In Vitro Effects of External Pressure Changes on the Sealing Ability under Simulated Diving Conditions. (15th October 2012) - Stoetzer, Marcus; Ruecker, Martin; Koch, Andreas; Ziebolz, Dirk; Kokemüller, Horst; Kaempf, Christina; Gellrich, Nils-Claudius; von See, Constantin
Abstract : Aim . To measure and validate the permeability of pressure changes in correlation to different root filling techniques. Methods . Eighty extracted single-rooted teeth were randomly assigned to one of eight groups of ten teeth. Following standardized instrumentation and irrigation, root canal fillings were performed using either cold lateral condensation, a warm carrier-based gutta-percha obturation technique, a warm carrier-based Resilon, or warm gutta-percha compaction with the downpack/backfill technique. After insertion of a pressure sensor within the pulp chamber ten teeth of each group then underwent simulated dives with pressure measurement and the other ten a dye penetration test during simulated dives to 5.0 bar. Differences were analyzed statistically (P < 0.05 ) using one-way analysis of variance (ANOVA). Results . When the warm carrier-based gutta-percha obturation technique and vertical gutta-percha obturation techniques were used, there was significant lower intrapulpal pressure to experimental chamber pressure (P > 0.05 ). When cold lateral condensation or carrier-based Resilon as used, pressure was sometimes almost completely equalized. Conclusions . Warm gutta-percha obturation techniques provide a largely pressure-tight seal whereas the Resilon obturation technique and cold lateral condensation appear to be unsuitable to pressure changes.